Recent Advances in Membrane-Coated Micro/Nanomotors in Biological Applications - Zhao K; Xu J; Song W; Cheng J; Al Mamun A; Tu Y; Xiao J; Wang S; Zhang N (International Journal of Nanomedicine)
Kaiting Zhao,1,* Jia Xu,2,* Wei Song,3 Jie Cheng,3 Abdullah Al Mamun,3 Yingfeng Tu,4 Jian Xiao,5 Shuanghu Wang,3 Ning Zhang1 1Department of Emergency, The Lishui Hospital of Wenzhou Medical University, The First Affiliated Hospital of Lishui University, Lishui People’s Hospital, Lishui, Zhejiang, 323000, People’s Republic of China; 2Department of Pharmacy, The Second Affiliated Hospital of Jiaxing University, Jiaxing, Zhejiang, 314000 People’s Republic of China; 3Key Laboratory of Joint Diagnosis and Treatment of Chronic Liver Disease and Liver Cancer of Lishui, The Lishui Hospital of Wenzhou Medical University, The First Affiliated Hospital of Lishui University, Lishui People’s Hospital, Lishui, Zhejiang, 323000, People’s Republic of China; 4School of Pharmaceutical Sciences, Guangdong Provincial Key Laboratory of New Drug Screening, Southern Medical University, Guangzhou, 510515, People’s Republic of China; 5Molecular Pharmacology Research Center, School of Pharmaceutical Sciences, Wenzhou Medical University, Wenzhou, Zhejiang, 325035, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shuanghu Wang, Key Laboratory of Joint Diagnosis and Treatment of Chronic Liver Disease and Liver Cancer of Lishui, The Lishui Hospital of Wenzhou Medical University, The First Affiliated Hospital of Lishui University, Lishui People’s Hospital, Lishui, Zhejiang, 323000, People’s Republic of China, Tel +86-18957091837, Email wangshuanghu@lsu.edu.cn Ning Zhang, Department of Emergency Medicine, The Lishui Hospital of Wenzhou Medical University, The First Affiliated Hospital of Lishui University, Lishui People’s Hospital, Lishui, Zhejiang, 323000, People’s Republic of China, Tel +86-18957090930, Email starstar314@163.comAbstract: The integration of synthetic micro/nanomotors (MNMs) with natural biomaterials derived from cell membranes has emerged as a highly promising strategy for advancing biological applications. The membrane-coated MNM offers distinct advantages over earlier MNMs dependent on chemical fuels such as hydrogen peroxide, which were prone to poor biocompatibility and harmful byproducts. These include enhanced biocompatibility, immune evasion via natural membrane surfaces, multifunctionality for drug delivery, self-propulsion in complex environments, self-degradation to reduce residual toxicity and inherent imaging capabilities enabling real-time tracking. This review provides a comprehensive overview of the integration of various types of micromotors with natural cell membranes commonly present in the circulatory system. Additionally, it summarizes the methodologies for the preparation, characterization and functional evaluation of biofilm-modified micromotors. The present article also critically examines current developments in biofilm-modified micromotors, addressing their challenges and limitations in enhancing clinical efficacy and facilitating transition to clinical trials in humans. Keywords: micro/nanomotors, nanodrugs, membrane-coated, self-propulsion, drug delivery